PENGARUH ANGGARAN FLEKSIBEL DALAM MENGAMBIL KEPUTUSAN MANAJERIAL (STUDI KASUS: PT. ES TONASA) - Salim, Dinul Fitria Nur; Hardiningsih; Rahmawati, Umi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
The purpose of this study was to determine the flexible budget comparison made by the Es Abadi Sorong company in analyzing managerial decisions. The method used in this research is descriptive research with a quantitative approach. Based on the results of comparing the flexible budget in terms of quantity. Depending on the high or low level of production will affect the budget costs to be incurred. With a total annual budget of Rp. 258,500,000 to (realization) Rp. 231,000,000. this appears to provide an advantage in choosing flexible budgets as managerial decision makers.